Analytical Method Development And Fundamental Studies On The Separation Of Drugs Using Capillary Electrophoresis - Al Azzam, Khaldun Mohammad Mitlaq (2011)
Capillary zone electrophoresis (CZE) methods for the simultaneous separation of the β-blocker drugs (atenolol (AT), chlorthalidone (CH) and amiloride (AM)), using UV and capacitively coupled contactless conductivity detectors (C4D) were developed and validated. Under the adopted conditions, the analytes were separated in less than 4 min and 7 min for the CZE-UV and the CZE-C4D methods, respectively. The CZE-C4D method has slightly inferior sensitivity, but nevertheless, both methods were successfully applied to the determination of the active ingredients in pharmaceutical preparations.